G322(P) Sudden deterioration of scoliosis – an atypical secondary sexual characteristic in children with severe disability. (7th April 2014) - Sutherland, A; Kanumakala, S; Campbell, V
Abstract : Background: Non ambulant children with cerebral palsy are at risk of progressive neuromuscular scoliosis, typically deteriorating during pubertal growth spurt. We present 2 girls in whom sudden deterioration of scoliosis, in retrospect, marked pubertal growth spurt, despite no evidence of usual secondary sexual characteristics or biochemical changes. Recognition of this allowed definitive spinal surgery to go ahead at the optimum time. Method: Notes and Xray review. Results: Case 1: This female child had severe cerebral palsy due to documented hypoxic ischaemic encephalopathy. From 7.5 years, there was sudden worsening of the scoliosis over the next 18 months (Cobb angle of 60 0 progressed to >100 0 ). She had been investigated for early puberty and had no clinical secondary sexual characteristics or biochemical evidence of precocious puberty. She underwent spinal fusion at just 8.8 years; subsequently she developed typical secondary sexual characteristics and menarche at 9.0 years. Case 2: This female child had severe cerebral palsy secondary to epileptic encephalopathy. Precocious puberty was evident aged 6 and she commenced GnRH analogue therapy (Decapeptyl 11.25 mg, 10 weekly). From 8.0 there was rapid worsening of her scoliosis with Cobb angle of 49 0 progressing to 92 0 two years later. Clinical & biochemical assessment suggested her precocious puberty to be well controlled. She underwent spinal fusion at 11 years, and developed secondary sexual characteristics soon after this. Discussion: Definitive scoliosis surgery is rarely considered before the teenage years, as it is assumed the spine has still to undergo its peak growth associated with puberty. However if correction is delayed after peak growth, the scoliosis curve stiffens, making the surgery more challenging to perform. The timing of puberty in children with severe disabilities can be hard to predict. Rapid progression of scoliosis indicated that spinal growth was occurring despite lack of usual secondary sexual characteristics associated with puberty. Treatment with GnRH analogues in the second case did not avoid skeletal sequelae of early puberty. Conclusion: Awareness of the skeletal manifestations in puberty can facilitate appropriate early operative management, halting further progression of scoliosis and its complications.